Nano‐hydrogel embedded with quercetin and oleic acid as a new formulation in the treatment of diabetic foot ulcer: A pilot study. Issue 2 (25th December 2019) - Gallelli, Giuseppe; Cione, Erika; Serra, Raffaele; Leo, Antonio; Citraro, Rita; Matricardi, Pietro; Di Meo, Chiara; Bisceglia, Francesco; Caroleo, Maria C.; Basile, Sonia; Gallelli, Luca
Abstract: Wound healing, especially diabetic ones, is a relevant clinical problem, so it is not surprising that surgical procedures are often needed. To overcome invasive procedures, several strategies with drugs or natural compound are used. Recently, in an experimental study, we described an increase in keratinocyte proliferation after their exposition to quercetin plus oleic acid. In the present clinical study, we evaluated both the clinical efficacy and the safety of nano‐hydrogel embedded with quercetin and oleic acid in the treatment of lower limb skin wound in patients with diabetes mellitus (DM). Fifty‐six DM patients (28 men and 28 women, mean age 61.7 ± 9.2 years) unsuccessfully treated with mechanical compression were enrolled and randomised to receive an add on treatment with hyaluronic acid (0.2%) or nano‐hydrogel embedded with quercetin and oleic acid. The treatment with nano‐hydrogel embedded with quercetin and oleic acid significantly ( P  < .01) reduced the wound healing time, in comparison to hyaluronic acid (0.2%) without developing of adverse drug reactions, suggesting that this formulation could be used in the management of wound healing even if other clinical trials must be performed in order to validate this observation.